2021
DOI: 10.3390/ma14174873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretreatment and Cryogenic Temperatures on Mechanical Properties and Microstructure of Al-Cu-Li Alloy

Abstract: The mechanical properties of Al-Cu-Li alloys after different pretreatments were investigated through tensile testing at 25 and −196 °C, and the corresponding microstructure characteristics were obtained through optical metallography, scanning electron microscopy, electron backscatter diffraction, and transmission electron microscopy. An increasing mechanism of both strength and ductility at cryogenic temperatures was revealed. The results show that the hot deformation pretreatment before homogenization promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This is attributed to Al 3 Zr pinning grain boundaries and inhibiting the growth of surface grains during static recrystallization. The effect of Al 3 Zr on reducing the coarse-grain layer thickness of Al-Cu-Li alloy has also been confirmed in another study on rolled plate by our research group (Wang et al, 2021).…”
Section: Om Observationsupporting
confidence: 73%
See 1 more Smart Citation
“…This is attributed to Al 3 Zr pinning grain boundaries and inhibiting the growth of surface grains during static recrystallization. The effect of Al 3 Zr on reducing the coarse-grain layer thickness of Al-Cu-Li alloy has also been confirmed in another study on rolled plate by our research group (Wang et al, 2021).…”
Section: Om Observationsupporting
confidence: 73%
“…In addition, its fine and continuous distribution can reduce the degree of recrystallization and improve mechanical properties (Tsivoulas and Robson, 2015). A 3 Zr dispersoids can effectively reduce the thickness of the coarse-grained layer, inhibit the local PFZ, and improve the properties of the Al-Cu-Li alloy (Wang et al, 2021). At present, there is no public report on the formation of Al 3 Zr dispersoids and CSE, and its coupling factors and mechanism still need to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…The strengthening mechanism of Al-Cu-Li alloy included solid solution strengthening, fine crystal strengthening, second phases particle strengthening and work hardening [31]. Due to the same chemical composition, composite spinning-extrusion forming process, solution treatment and T8 heat treatment of the four samples, the strength difference at T8 were mainly due to the precipitation of aging strengthened phase and the contribution of grain refinement.…”
Section: Strengthmentioning
confidence: 99%
“…Numerous studies on aluminum alloys in cryogenic environments found that the strength of aluminum alloys increases with decreasing temperatures [5][6][7][8][9][10][11]. Wang et al [5] compressed 7A85 aluminum alloy forgings at room temperature and low temperatures, followed by solution treatment and aging.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, although there have been many studies on aluminum alloys in cryogenic environments, these studies mainly focus on cryogenic plastic deformation processes [5][6][7][8][9][10][11]. The alloy states studied are mostly annealed, solution-treated, and homogenized, with less research being conducted on aging-state aluminum alloys.…”
Section: Introductionmentioning
confidence: 99%